Principialismo, garantismo, reglas y derrotabilidad en el control constitucional de las leyes penales (2015)
The legal theory regarding Criminal Law limits’ has not reached a perfect development. This is particularly true as long as it has not been defined and interpreted in the light of the different legal rationales, namely the legislative, judicial